A book by the German Scientist on the National Minority of Prussian Lithuanians - Arnaszus, Helmut Hans Jurgen (Knygotyra, 2018)
KLEIN, MANFRED. PREUSSENS LITAUER: STUDIEN ZU EINER (FAST) VERGESSENEN MINDERHEIT. HAMBURG: VERLAG DR. KOVAČ GMBH, 2017. 272 S. (SCHRIFTENREIHE „SCHRIFTEN ZUR KULTURWISSENSCHAFT“, BD. 119). ISBN 978-3-8300-9732-7.